PENGARUH DUKUNGAN MANAJEMEN PUNCAK, KETERLIBATAN PENGGUNA, PROGRAM PELATIHAN TERHADAP KINERJA SIA PADA BPR DI KEDIRI - Wulandari, Putri Syintia; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
Assessment performance of Accounting Information Systems used by company is very important to know. SIA performance can not be separated from the factors that can affect it. This study was conducted to determine the effect of top management support, user involvement in the application of the system, and user training program on performance SIA BPR district of Kediri, Tabanan regency. Sampling technique used is the census sampling technique (saturated sample) and get 60 samples. The data collection is done by survey method, which is distributing questionnaires to employees who work with computerized systems on BPR in the district of Kediri. In this research, engineering analysis conducted is multiple linear regression analysis. The analysis showed that the top management support, user training programs, and the involvement of users in the application of the system positively affects to performance of Accounting Information System.
Keywords: management support system, involvement of users, user training program, accounting information system performance, bpr